‘Catch as Catch Can’ - van Eijck van Heslinga, Els (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2002)
Having been asked to speak on security prevention and actual incidents, I will start with the latter. After some sad stories, I would like to give a more general analysis, and then I will explain our thinking in the Koninklijke Bibliotheek on the steps we can take in order to prevent theft as far as possible in the future.